Ruthenium(ii) complexes of pyridinol and N-heterocyclic carbene derived pincers as robust catalysts for selective carbon dioxide reduction. Issue 81 (28th September 2017) - Boudreaux, Chance M.; Liyanage, Nalaka P.; Shirley, Hunter; Siek, Sopheavy; Gerlach, Deidra L.; Qu, Fengrui; Delcamp, Jared H.; Papish, Elizabeth T.
Abstract : New methoxy substituted CNC pincers form ruthenium catalysts that are robust and convert CO2 to CO selectively using light energy. Abstract : A new pincer ligand with N-heterocyclic carbene (NHC) and 4-pyridinol-derived rings supports ruthenium complexes for photocatalytic CO2 reduction. The methoxy group on the pyridine ring offers unique catalysis advantages not seen with the unsubstituted analog. Our best catalyst offers selective CO formation, ∼250 turnover cycles, and a 40 h lifetime.